2005
DOI: 10.1185/030079905x38196
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of lumiracoxib 100 mg once daily in knee osteoarthritis: a 13-week, randomized, double-blind study vs. placebo and celecoxib

Abstract: Lumiracoxib 100 mg od provided effective relief from the pain of knee OA, with efficacy similar to celecoxib 200 mg od, and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 13 publications
1
50
0
Order By: Relevance
“…There has been some evidence of an increased placebo response among African American patients in clinical trials for depression and schizophrenia, compared with white patients. 37,38 Response to NSAIDs in African Americans with OA Elevated rates of placebo response have been reported in other OA trials, 39,40 and a study to evaluate baseline factors as a prediction of placebo response in a large OA study concluded that placebo responders were more likely to report moderate levels of pain at baseline. 41 In the latter study, patients from the placebo arm of a trial evaluating the effects of risedronate on pain and joint space narrowing in knee OA were stratified according to 20% and 50% declines in WOMAC pain scores between baseline and 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some evidence of an increased placebo response among African American patients in clinical trials for depression and schizophrenia, compared with white patients. 37,38 Response to NSAIDs in African Americans with OA Elevated rates of placebo response have been reported in other OA trials, 39,40 and a study to evaluate baseline factors as a prediction of placebo response in a large OA study concluded that placebo responders were more likely to report moderate levels of pain at baseline. 41 In the latter study, patients from the placebo arm of a trial evaluating the effects of risedronate on pain and joint space narrowing in knee OA were stratified according to 20% and 50% declines in WOMAC pain scores between baseline and 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…AUSCAN, Australian/Canadian OA Hand Index; bid, twice daily; CX, celecoxib; db, double-blind; dd, double-dummy; DPDA, difficulty in performing daily activities; LSM, least squares mean; LX, lumiracoxib; mc, multicenter; NR, not reported; OA, osteoarthritis; od, once daily; PL, placebo; RCT, randomized controlled trial; RX, rofecoxib; wk, week; WOMAC, Western Ontario and McMaster Universities OA Index. (Schnitzer et al 2004b;Lehmann et al 2005;Sheldon et al 2005), one RCT published in abstract form (Pavelka et al 2005), and an additional analysis from TARGET published in abstract form , has shown that the pain relief [as assessed by pain intensity on a visual analog scale (VAS)] with lumiracoxib is superior to that gained with placebo and similar to that with celecoxib, rofecoxib, ibuprofen, naproxen, and diclofenac in patients with OA of the hand, hip, or knee (Tables 3 and 4). The efficacy of lumiracoxib does not appear to be dose dependent, with the 100 mg dose providing similar efficacy to the 400 mg dose.…”
Section: Pain Intensitymentioning
confidence: 99%
“…Level 1 ) and level 2 evidence (Lehmann et al 2005;Sheldon et al 2005) demonstrated that lumiracoxib improves joint stiffness and overall function [assessed using the difficulty in performing daily activities (DPDA) and stiffness subscales of the WOMAC questionnaire or the AUSCAN] compared with placebo (Table 5). These improvements were similar to that achieved with diclofenac and celecoxib, and are expected to have a positive impact on the quality of life of the patient.…”
Section: Joint Stiffness and Functionmentioning
confidence: 99%
See 2 more Smart Citations